Has the risk of mortality related to short-term exposure to particles changed over the past years in Athens, Greece?. (April 2018) - Tzima, K.; Analitis, A.; Katsouyanni, K.; Samoli, E.
Abstract: Although the health effects of short-term exposure to ambient particles have been well documented, there is a need to update scientific knowledge due to the continuously changing profile of the air pollution mixture. Furthermore the effect of the severe economic crisis in Greece that started in 2008 on previously reported associations has not been studied. We assessed the change in mortality risk associated with short-term exposure to PM10 in Athens, Greece during 2001–12. Time-series data on the daily concentrations of regulated particles and all cause, cardiovascular and respiratory mortality were analyzed using overdispersed Poisson regression models, controlling for time-varying confounders such as seasonality, meteorology, influenza outbreaks, summer holidays and day of the week. We assessed changes in risk over time by inclusion of an interaction term between particles' levels and time or predefined periods, i.e. 2001–07 and 2008–12. While the related mortality risks increased over the analyzed period, the difference before and after 2008 was significant only for total mortality (p-value for interaction .03) and driven by the difference observed among those ≥75 years. An interquartile increase in PM10 before 2008 was associated with 1.51% increase in deaths among ≥75 years (95% Confidence interval (CI): 0.62%, 2.40%), while after 2008 with a 2.61% increase (95%CI: 1.72%, 3.51%) (p-value for interaction .01). Our results indicate that despite the decline in particles' concentration in Athens, Greece during 2001–12 the associated mortality risk has possibly increased, suggesting that the economic crisis initiated in 2008 may have led to changes in the particles' composition due to the ageing of the vehicular fleet and the increase in the use of biomass fuel for heating. Highlights: Mortality risks associated with PM10 exposure increased after 2008. Increases were significant for total and cardiovascular mortality among ≥75 years. The economic crisis initiated in 2008 may have changed particles' toxicity.